Effect of the intra-perovskite lattice copper on the reducibility of La(Co,Cu)O3. - Thảo, Nguyễn Tiến; Thuận, Ngô Thị; Kaliaguine, Serge (Vietnam Journal of Chemistry, 2012)
Nanocrystalline La(Co,Cu)O3 perovskites have been characterized by several techniques including N2 absorption/desorption, X-ray diffraction, Temperature-Programmed Reduction (H2-TPR), Temperature-Programmed Oxidation (O2-TPO). H2-TPR and O2-TPO results indicate that the reducibility of Co3+ in the ground La(Co,Cu)O3 perovskites was promoted by the presence of the intra- lattice copper. An increased copper content leads to a decreased reduction temperature of Co3+ to Co0 and an increased dispersion of metallic copper-cobalt phase. The XRD and H2-TPR studies also revealed that the perovskite structure of La(Co,Cu)O3 is somewhat less stable than the-ones of LaCoO3.